Is anybody listening? The nature of second language listening in integrated listening-to-summarize tasks. (January 2020) - Rukthong, Anchana; Brunfaut, Tineke
Integrated test tasks, such as listening-to-speak or reading-to-write, are increasingly used in second language assessment despite relatively limited empirical insights into what they assess. Most research on integrated tasks has primarily focused on the productive skills involved; studies exploring the receptive skills mostly investigated tasks with reading input. Little is known about the nature of listening comprehension in integrated listening-to-write or listening-to-speak tasks. This study therefore investigates the listening construct underlying integrated tasks with oral input and its effect on summary accuracy. Eight listening-to-summarize tasks (four listening-to-speak, four listening-to-write) were administered to 72 Thai-L1, English-L2 students. Sixty participants provided their views on sources of listening difficulty through post-task questionnaires. Twelve participants produced stimulated recalls on their listening comprehension processing. The analyses of the recalls, combined with participants' listening notes and oral/written summaries, revealed participants' use of several cognitive listening processes and their monitoring through (meta)cognitive strategies, functioning interactively and interdependently in complex ways. The use of listening processes and strategies varied between tasks with different listening inputs, partly owing to differences in the passages' linguistic difficulty (as perceived by the participants). However, the successful application of these processes and strategies (and their combinations) proved to be a prerequisite for producing accurate summaries.